2002
DOI: 10.1007/bf02817647
|View full text |Cite|
|
Sign up to set email alerts
|

Mycoremediation of PAH-contaminated soil

Abstract: Out of a number of white-rot fungal cultures, strains of Irpex lacteus and Pleurotus ostreatus were selected for degradation of 7 three- and four-ring unsubstituted aromatic hydrocarbons (PAH) in two contaminated industrial soils. Respective data for removal of PAH in the two industrial soils by I. lacteus were: fluorene (41 and 67%), phenanthrene (20 and 56%), anthracene (29 and 49%), fluoranthene (29 and 57%), pyrene (24 and 42%), chrysene (16 and 32%) and benzo[a]anthracene (13 and 20%). In the same two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 20 publications
0
21
1
2
Order By: Relevance
“…in solid wheat straw substrate, Wolter et al (1997) showed that by week 15 of incubation, the degradation efficiency of BaA was 25%. Generally, lowmolecular weight PAHs possessing two or three aromatic rings, such as Ace are easily degraded, while those with high-molecular weight, such as BaA are significantly more recalcitrant in soils (Kanaly and Harayama 2000;Bhatt et al 2002). However, in the present study, the tested P. ostreatus strain under our experimental conditions degraded BaA to a greater extent than Ace.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…in solid wheat straw substrate, Wolter et al (1997) showed that by week 15 of incubation, the degradation efficiency of BaA was 25%. Generally, lowmolecular weight PAHs possessing two or three aromatic rings, such as Ace are easily degraded, while those with high-molecular weight, such as BaA are significantly more recalcitrant in soils (Kanaly and Harayama 2000;Bhatt et al 2002). However, in the present study, the tested P. ostreatus strain under our experimental conditions degraded BaA to a greater extent than Ace.…”
Section: Resultscontrasting
confidence: 51%
“…The hazards associated with PAHs can be overcome by the use of conventional physicochemical remediation methods; however, these are expensive, and in many cases, transfer the pollutant from one phase to another. Fungal degradation is often characterised as an environmentally friendly and costeffective approach to remove PAHs from soil (Bhatt et al 2002;Gao et al 2010). A number of species of ligninolytic fungi, such as Pleurotus ostreatus , are known to degrade PAHs and the biodegradation rates correlate with the production of ligninolytic enzymes (Bamforth and Singleton 2005;Johnsen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible alternatives for the degradation of this type of compounds is the use of white rot fungi YESILADA 2004, YESILADA et al 2003). These fungi can remove a wide variety of structurally diverse pollutants (BHATT et al 2002, KAHRAMAN et al 2005, ASMA and YESILADA 2000, UNYAYAR and MAZMANCI 2005 , SANI et al 1998, AKSU and TEZER 2000, ZILLY et al 2002.…”
mentioning
confidence: 99%
“…Generally, several studies in literature have specified clean-up techniques for PAH contaminated sites using bacterial cultures, pure strains, or strains in association (Boochan et al, 2000;Bhatt, 2002;Reardon et al, 2002;Janikowski et al, 2004;Xu and Obbard, 2004;de Lucas et al, 2005). The few available reports on the modeling of PAH degradation (Tabak and Govind, 1997;Rogers and Reardon, 2000) have however, been unable to perform optimally relative to availability, mobility, toxicity, and concentration of PAHs in the soil system ranging from surface soils to deep aquifers.…”
Section: Introductionmentioning
confidence: 96%